2005
DOI: 10.1080/09513590400021136
|View full text |Cite
|
Sign up to set email alerts
|

Sexual hormone serum levels and temporomandibular disorders. A preliminary study

Abstract: The aim of the present study was to investigate the role of sexual hormones in a young adult population affected by articular forms of temporomandibular disorders (TMD), measuring 17beta-estradiol and progesterone serum levels. In the study, we included 40 patients (20 males and 20 females) with a Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) axis I group II diagnosis of disk displacement and/or group III diagnosis of arthralgia, osteoarthritis or osteoarhrosis, and 32 healthy controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
4
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 12 publications
2
42
4
2
Order By: Relevance
“…The preponderance of women in the present study is consistent with previous findings (6). Attempts to explain female dominance among TMJD patients have identified several potential predisposing factors, including the effects of gonadal hormones such as estrogen, progesterone, and relaxin (17,18). These hormones are believed to have a degenerative effect on the disc and/or bone of the mandibular condyle.…”
Section: Discussionsupporting
confidence: 82%
“…The preponderance of women in the present study is consistent with previous findings (6). Attempts to explain female dominance among TMJD patients have identified several potential predisposing factors, including the effects of gonadal hormones such as estrogen, progesterone, and relaxin (17,18). These hormones are believed to have a degenerative effect on the disc and/or bone of the mandibular condyle.…”
Section: Discussionsupporting
confidence: 82%
“…The mechanisms underlying these sex-related differences remain obscure and likely involve both psychologic and physiologic factors [4]. The role of the sexual hormones (estrogens) which appear to alter the excitability of trigeminal afferent fibers to noxious stimulation of craniofacial tissues, is supported by several human [35][36][37] and animal [13] studies. However, the effect of estrogens in the etiology of TMD seems complex and could depend upon various conditions, for example the acute (antiinflammatory effect) or chronic (tissular destruction) nature of the pain [7].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to RA, TMDs are approximately twice as prevalent (and more severe) in women than in men (6,7). Sex hormones, particularly estrogens, are reported to be involved in TMD (6,(8)(9)(10). We also previously reported that estrogen aggravates TMJ inflammation through the induction of proinflammatory cytokines in the synovial membrane (11).…”
mentioning
confidence: 90%